2019
DOI: 10.1097/md.0000000000014335
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and risk of salmonella infection

Abstract: Helicobacter pylori ( H pylori ) infection is the most frequent infection worldwide and it has been postulated that it predisposes to multiple enteric pathogens and diarrheal diseases. Salmonella infection is common in tropical and under developed communities and is associated with wide range of diseases from gastroenteritis to typhoid fever. This study aimed at detecting the impact of H pylori infection on the incidence of salmonella infections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…pylori prevalence varies among countries; generally, the prevalence is about 30% in developed and up to 80% in developing countries. [16][17][18] This was similar to our results, as we found that H. pylori prevalence was 83.3% among the participants in the study. NAFLD was significantly higher in H. pylori (+ve) group than H. pylori (−ve) group.…”
Section: Discussionsupporting
confidence: 90%
“…pylori prevalence varies among countries; generally, the prevalence is about 30% in developed and up to 80% in developing countries. [16][17][18] This was similar to our results, as we found that H. pylori prevalence was 83.3% among the participants in the study. NAFLD was significantly higher in H. pylori (+ve) group than H. pylori (−ve) group.…”
Section: Discussionsupporting
confidence: 90%
“…However, H. pylori infection can induce inflammatory responses as well as production of pro-inflammatory cytokines, and leads to malabsorption of essential nutrients [8]. Infection with H. pylori may also predisposes to multiple enteric pathogens resulting is altered intestinal health and function [8,21].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The prevalence of H. Pylori changed among countries generally. The prevalence is about 30% in developed countries and about 80% in developing countries [12].…”
Section: Discussionmentioning
confidence: 99%